2019
DOI: 10.3390/ijerph16214155
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Analysis of the Prevalence of Female Genital Mutilation/Cutting among 0–14-Year-Old Girls in Kenya

Abstract: Female genital mutilation/cutting (FGM/C), also known as female circumcision, is a global public health and human rights problem affecting women and girls. Several concerted efforts to eliminate the practice are underway in several sub-Saharan African countries where the practice is most prevalent. Studies have reported variations in the practice with some countries experiencing relatively slow decline in prevalence. This study investigates the roles of normative influences and related risk factors (e.g., geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…These results agreed with findings from previous studies [11,17,[27][28][29][45][46][47]. For example, it was found that education plays an important role in a mother's decision on whether her daughter will be cut or not [27], with mother's who had higher education less likely to cut their daughters in Nigeria [11].…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…These results agreed with findings from previous studies [11,17,[27][28][29][45][46][47]. For example, it was found that education plays an important role in a mother's decision on whether her daughter will be cut or not [27], with mother's who had higher education less likely to cut their daughters in Nigeria [11].…”
Section: Plos Onesupporting
confidence: 90%
“…A study conducted in Senegal, Burkina Faso and Egypt by Farina and Ortensi found higher FGM/C prevalence among girls whose mothers had undergone FGM/C [46]. In the same spirit, studies conducted in the context of Kenya found that a woman's FGM/C status was key to her support for the continuation of the practice [28], and that daughters of women who were cut, women who supported FGM/C continuation and women who believed that FGM/C was a religious obligation, were more likely to be cut than their peers [29].…”
Section: Plos Onementioning
confidence: 95%
See 1 more Smart Citation
“…The Female Genital Mutilation/Cutting (FGM/C), or female circumcision, is another common form of violence against women in sub-Saharan African countries. It is a practice determining the removal of all or part of the external female genital in the absence of medical needs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Kenia, a study conducted on 0–14-year-old girls showed that daughters of cut women were highly likely to live the same experience. The likelihood of a girl being mutilated increased with the proportion of women who were cut, who supported FGM/C continuation, and who believed FGM/C was a religious obligation [ 31 ]. Achia [ 35 ], found a correlation between a woman’s current FGM/C status and her support for the continuation of the practice, among 15-49 years old women.…”
Section: Resultsmentioning
confidence: 99%